Rudra Mahāvīra: Vrātya Elements in the Vedic Pravargya-Complex - af Edholm, Kristoffer (Studia Orientalia Electronica, 2021)
This study reviews the arguments of previous publications, and adds new ones, for establishing connections between the Vedic pravargya-complex (the rituals, stanzas, and mythology of the pravargya), the vrātya, and the deity Rudra. These connections include Rudra as Mahāvīra (the epithet given to a deity and a vessel in the pravargya), the sattra setting of the pravargya’s paradigm-myth, the motif of the unstrung bow, the theme of exclusion, and the divinisation of man as a goal of the ritual. It is argued that the superhuman status attributed to Mahāvīra is comparable with that of characters celebrated in the Ṛgveda and Atharvaveda, such as the ekavrātya, brahmacārin, and keśin. The affinity between these figures may be derived from a common ideology, with the roots of some of them to be sought in the Indo-European warrior-society and male rites de passage.